Is compromised oral health associated with a greater risk of mortality among nursing home residents?: a controlled clinical study - Klotz, Anna-Luisa; Hassel, Alexander J.; Schröder, Johannes; Rammelsberg, Peter; Zenthöfer, Andreas (Aging clinical and experimental research, 2017)
The objective of this controlled clinical study was to evaluate the association between oral health and 1-year mortality among nursing home residents with or without oral health intervention. METHODS: This research was part of a multidisciplinary intervention study (EVI-P) performed in 14 nursing homes in Germany. Two-hundred and nineteen nursing home residents were included in the study and assigned to an intervention group, for which dental health education was offered and ultrasonic baths were used for denture cleaning (n = 144), or to a control group (n = 75). Before the intervention, each participant was examined, and dental status, plaque control record (PCR), Denture Hygiene Index, and results from the Revised Oral Assessment Guide were recorded. Amount of care needed and dementia were also assessed, by use of the Barthel Index and the Mini Mental State Examination, respectively. Participant mortality was determined after 12 months, and bivariate analysis and logistic regression models were used to evaluate possible factors affecting mortality. RESULTS: Bivariate analysis detected a direct association between greater mortality and being in the control group (p = .038). Participants with higher PCR were also more likely to die during the study period (p = .049). For dentate participants, the protective effect of being in the intervention group was confirmed by multivariate analysis in which covariates such as age and gender were considered. CONCLUSION: Oral hygiene and oral health seem to affect the risk of mortality of nursing home residents. Dental intervention programs seem to reduce the risk of 1-year mortality among nursing home residents having remaining natural teeth. Further studies, with larger sample sizes and evaluation of the causes of death, are necessary to investigate the reasons for these associations.